2006 IEEE International Symposium on Performance Analysis of Systems and Software
DOI: 10.1109/ispass.2006.1620787
|View full text |Cite
|
Sign up to set email alerts
|

Branch trace compression for snapshot-based simulation

Abstract: We present a scheme to compress branch trace information for use in snapshot-based microarchitecture simulation. The compressed trace can be used to warm any arbitrary branch predictor's state before detailed microarchitecture simulation of the snapshot. We show that compressed branch traces require less space than snapshots of concrete predictor state. Our branch-predictor based compression (BPC) technique uses a software branch predictor to provide an accurate model of the input branch trace, requiring only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…It was shown that the compressors generated by TCgen have a very high compression ratio [5,16]. Another predictor-based compressor was proposed by Barr and Asanović but specialized for control-flow traces [2]. The compression method proposed by Marathe et al targets trace records consisting of one instruction address and one data address [15].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that the compressors generated by TCgen have a very high compression ratio [5,16]. Another predictor-based compressor was proposed by Barr and Asanović but specialized for control-flow traces [2]. The compression method proposed by Marathe et al targets trace records consisting of one instruction address and one data address [15].…”
Section: Related Workmentioning
confidence: 99%
“…We have chosen a VPC-like compressor/decompressor that matches approximately the amount of memory used by the big bytesort. We used the following TCgen specification : 0-Bit Header; 64-Bit Field 1 = L1 = 1, L2 = 1048576: DFCM3 [2], FCM3 [3], FCM2 [3], FCM1 [3]; ID = Field 1; Compressor = 'bzip2 -c -z -9'; Decompressor = 'bzip2 -c -d'; . This compressor/decompressor uses 232 Mbytes of memory.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of trace-specific compression techniques have been proposed [8][9][10]. However, they are mainly focused on software-based compression, combining trace-specific compression with a general-purpose compression algorithm, such as gzip or bzip2.…”
Section: Introductionmentioning
confidence: 99%